Constraints on alternative cosmological models from clustering and redshift-space distortions (2019)
In this Thesis I have exploited the most recent observational data from CMB, BAO and growth rate of LSS as well as N-body simulations of modified gravity, to investigate the spatial properties of the large scale structure of Universe by constraining cosmological parameters in the framework of alternative cosmologies. The research is focused on clustering and redshift space distortions as cosmological probe. In this context I have studied the degeneracies between modified gravity and massive neutrinos as well as the robustness of the methodology for constraining the linear growth rate including realistic systematics, implementing suitable parametrizations of the redshift-space distortions in the perspective of current and future galaxy surveys.